HUBUNGAN PENGETAHUAN PENGGUNAAN TANAMAN HERBAL DENGAN PERILAKU PEMANFAATAN TANAMAN HERBAL UNTUK PENANGANAN HIPERTENSI - Dwi Kasfarina; Fajarina Lathu Asmaran; Adi Sucipto (Universitas Muhammadiyah Klaten, 2023)
Hypertension is a condition of systolic and diastolic blood pressure exceeding 140/90 mmHg. The use of herbs can help deal with hypertension. However, people don't know much about the kinds of herbs that can be used to treat hypertension. To learn the relationship between knowledge about the use of herbal plants and the behavior of the use of herb plants for the treatment of hypertension in Posbindu Linggang Purwodadi, West Kutai. Cross-sectional research design with an observational approach. The population in the study is an active member who follows the activities of Posbindu in Linggang Purwodadi each month on the criterion of having a history of hypertension. The sampling method used is a total sample with a total of 30 respondents. The data analysis test used is chi square. Respondents who have a lower level of knowledge and have used herbs include as many as 86.7%, or 26 respondents. The data was analyzed using the chi square formula with the Fisher exact alternative test with a p value of 1,000 > 0,005. There is no knowledge of the use of herbal plants and the behavior of herbal plant use for the treatment of hypertension in POSBINDU Linggang Purwodadi, West Kutai.